2010
DOI: 10.1080/03602559.2010.496418
|View full text |Cite
|
Sign up to set email alerts
|

Polyamide-6/Poly(lactic acid) Blends Compatibilized by the Maleic Anhydride Grafted Polyethylene-Octene Elastomer

Abstract: To evaluate the feasibility of a strategy to partially replace polyamide-6 (PA6) with poly(lactic acid) (PLA), the morphology, mechanical, and thermal properties of PA6/PLA blending systems were investigated. Polyethylene-octene elastomer (POE) and POE grafted with maleic anhydride (POE-g-MAH) are added to improve the impact strength and elongation at break of the blend. The results show that POE-g-MAH is an effective compatibilizer for PA6/PLA blending system. Compared with the morphology of PA6/PLA/ POE, sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Moreover, attaining high performance properties of the former by the latter is not yet possible. To overcome these limitations, partially degradable polymers have been developed with a negotiation between cost and performance [20][21][22]. Therefore, the investigations concerning the total or partial substitution of synthetic plastics by biodegradable materials have proven to be very useful in solving the problem of plastic waste management to a significant extent [8,14,15,[23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, attaining high performance properties of the former by the latter is not yet possible. To overcome these limitations, partially degradable polymers have been developed with a negotiation between cost and performance [20][21][22]. Therefore, the investigations concerning the total or partial substitution of synthetic plastics by biodegradable materials have proven to be very useful in solving the problem of plastic waste management to a significant extent [8,14,15,[23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Anderson and Hillmyer [20] investigated PLLA/PE blends and found that the impact properties of the composites were highly dependent on the dispersed-phase properties. Wang et al [21] studied polyamide 6 (PA6)/PLA/maleic anhydride-grafted poly (orthoester) (POE-g-MAH) blends and found that they were an effective compatibilizer for PA6/ PLA, which improved the impact strength of the blends significantly. Except for biocompatibility and biodegradability, thermoplastic polyolefin is more preponderant in many aspects, such as cost, mechanical properties and processibility, compared with many other biodegradable polymers in modifying PLA.…”
Section: Introductionmentioning
confidence: 98%
“…Previously, attempts were made to produce such materials via blending of PLA with polyamide-6 (PA-6) [9][10][11] through the introduction of a compitibilizing copolymer into the blend [12,13] and via blending of PLA with PA-11 and PA-12 [14,15]. Nevertheless, there were no macromolecular reactions between PLA (Bioflex ® ) and PA-6 in [9,10]; that is, the reactive compatibilization did not start, as evidenced by the selective extraction.…”
Section: Introductionmentioning
confidence: 99%